(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Workplace safety policies are crucial for enhancing productivity and fostering a positive work environment. Various psychological and physical factors influence workplace dynamics, making it essential to understand their interactions for effective management. Ensuring a safe and secure work environment increases employee engagement, reduces absenteeism, and fosters a culture of accountability, ultimately improving organizational efficiency. This systematic review examines the effectiveness of workplace safety policies on employee behavior and productivity by analyzing factors such as toxic workplace environments, managerial roles, and safety frameworks. By prioritizing robust safety measures, organizations can enhance employee well-being, improve work culture, and drive overall success. The study identified 21 relevant research papers through an extensive bibliographic search across multiple academic databases, including PubMed, Google Scholar, CINAHL, and ProQuest, covering studies published between 1990 and 2025. The PICO methodology was employed to structure the research approach and refine key concepts. Findings indicate that workplace safety policies significantly impact employee behavior, highlighting the necessity of effective regulations and interventions. Implementing long-term studies and controlled trials can help organizations refine safety protocols, reduce workplace risks, and improve productivity. Ultimately, prioritizing workplace safety benefits employees and strengthens overall industry performance.